Gastric cancer organoids: a promising model for personalized treatment of gastric cancer - Chang, Yu; Liu, Yu; Zhang, Huahua; Lei, Xia; Hu, Yunfeng (Frontiers in Cell and Developmental Biology, 2026)
Gastric cancer is one of the most prevalent malignant tumors in the gastrointestinal tract. At present, the main treatment methods of gastric cancer include chemotherapy, targeted therapy and immunotherapy. However, due to the strong heterogeneity of tumor cells, the current treatment schemes have different effects on each patient. Therefore, individualized treatment strategies for different patients have become an inevitable trend. The organoid model is an emerging technology for three-dimensional (3D) cell culture in vitro, which can simulate the three-dimensional structure of real organs and the interaction between cells, while retaining the heterogeneity of patients’ tumor cells. The response of organoid model to treatment can replace the response of patients’ tumor cells to treatment. Organoid model of gastric cancer can effectively bridge the basic research and clinical practice, and show remarkable transformation potential and broad application prospects in promoting individualized treatment of gastric cancer. In this paper, the establishment methods of organoid model of gastric cancer are systematically reviewed, and its application in drug sensitivity detection, biomarker discovery and mechanism research is discussed, in order to provide theoretical basis and practical reference for the development of precise treatment strategy for gastric cancer.